Discrepancy between Motor and Cognitive Control in Adults with Intellectual Disabilities - Hirata, Shogo; Okuzumi, Hideyuki; Kitajima, Yoshio; Hosobuchi, Tomio; Kokubun, Mitsuru (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
Purpose: To investigate the relationship between motor and cognitive control in adults with intellectual disabilities (ID), focusing on two aspects, speed and accuracy. Method: Participants were 62 adults with ID aged 20 to 47 years. Their intelligence quotients (IQ) ranged from 13 to 61. Nine of the adults with ID had Down syndrome, and 8 of the adults had autism. We conducted three tasks: seal affixation task, tray-carrying task, and the Matching Familiar Figures Test (MFFT). The seal affixation and tray-carrying tasks are motor tasks we devised that can separately measure the speed and accuracy of motor control. MFFT is a cognitive control task that can be used to evaluate cognitive styles, such as impulsive-reflective. Results: Adults with ID showed high motor accuracy and similar motor speed regardless of their MFFT performance. That is, discrepancies between motor and cognitive control existed in adults with ID. Conclusions: The results of this study indicate that some types of motor control problem may become unclear with growth. A longitudinal investigation focused on the motor skill development of persons with ID is therefore necessary.